Design of new cold rolled purlins by experimental testing and Direct Strength Method. (September 2017) - Nguyen, V.B.; Pham, C.H.; Cartwright, B.; English, M.A.
Abstract: New cold roll formed channel and zed sections for purlins, namely UltraBEAM™2 and UltraZED™2, have been developed by Hadley Industries plc using a combined approach of experimental testing, finite element modelling and optimisation techniques. The new sections have improved strength to weight ratio by increasing the section's strength through the use of stiffeners in the section webs. The European standard, Eurocode 3 [1], uses the traditional Effective Width Method to determine the strength of a cold formed steel member. However, the design of the new sections UltraBEAM™2 and UltraZED™2 using this method is very complicated in calculating the effective section properties as these sections contain complex folded-in stiffeners. In addition, the incorporation of competing buckling modes such as distortional buckling of these sections can be difficult to analyse. To overcome difficulties of using Eurocode 3 or such a standard with the Effective Width Method for determining the strength of these sections, the Direct Strength Method is adopted in this paper. Four-point beam bending tests were carried out to determine the buckling and ultimate bending capacities of the UltraBEAM™2 and UltraZED™2 sections. Results from both experimental testing and Finite Element analysis were initially used as validation for the design using the Direct Strength Method. The Direct Strength Method's results were then compared with the experimental test results for a broader data in which the UltraBEAM™2 and UltraZED™2 sections had a range of different width-to-thickness ratios. It showed an excellent agreement between test and Direct Strength design values suggesting that the Direct Strength Method is a powerful tool for the design and optimisation of the new cold roll formed channel and zed purlins. Highlights: Direct Strength Method (DSM) was used for design of new cold rolled channel and zed purlins. Bending tests and buckling/ultimate strength of the new sections were investigated. FE simulations of bending tests were established and compared with DSM and tests. The DSM predicted strength values correlated well with experimental and FE results.